Uji Sensitivitas dan Spesifisitas Hasil Pemeriksaan Mikroskopis Sputum BTA dengan Tes Cepat Molekuler (TCM) Pada Suspek Tuberkulosis Paru - Dewi Andini; Roni Afriansya; Wagiyo Wagiyo; Ahmad Riadi (Universitas Pahlawan Tuanku Tambusai, 2025)
Tuberculosis (TB) remains a major health issue in Indonesia, with a high incidence rate. Microscopic sputum BTA examination and the Molecular Rapid Test (MRT) GeneXpert are two commonly used diagnostic methods. However, the accuracy of these methods is still a concern, particularly in detecting cases with a low bacterial load. This study aims to determine the differences in sensitivity and specificity between microscopic sputum BTA examination and the Molecular Rapid Test in patients suspected of pulmonary TB. A cross-sectional design with a quantitative analytical observational approach was used. Samples consisted of suspected TB patients examined using both BTA and TCM methods at Balkesmas, Semarang area. Data were analyzed using sensitivity and specificity statistical tests and chi-square analysis. The study showed that TCM had higher sensitivity and specificity compared to the microscopic BTA method in detecting Mycobacterium tuberculosis. There was a significant difference between the results of the two methods. MRT proved to be superior in terms of sensitivity and specificity compared to microscopic sputum BTA examination. These findings may serve as a clinical consideration in selecting a more effective diagnostic method for pulmonary TB.